Method for rapidly densifying carbon fiber composite material
By performing fixing agent spraying and multi-stage deposition adjustments during the CVI density enhancement process of carbon fiber composites, the problem of uneven density enhancement in the prior art is solved, and uniform density enhancement and performance improvement of carbon fiber composites are achieved.
Patent Information
- Application Number
- CN202510079509.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-18
- Publication Date
- 2025-04-15
AI Technical Summary
There are problems of temperature difference and uneven density efficiency in the process of chemical vapor deposition (CVI) density enhancement of existing carbon fiber composite materials, resulting in uneven density enhancement of single disks and material columns.
The resin spraying equipment is used to spray the fixing agent on the surface of the carbon fiber preform and cure it at low temperature to reduce the predeposition process; in the deposition furnace, carbon source gas is introduced into the deposition gas for multi-stage deposition to ensure density uniformity.
The uniform density of carbon fiber composite materials is achieved, the density difference of the whole furnace is reduced, the consistency of products is improved, the mechanical properties and thermal conductivity of the carbon ceramic brake disc are enhanced, and its reliability and durability are improved.
Smart Images

Figure CN119822861A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon-ceramic brake discs, and in particular relates to a method for rapidly densifying a carbon fiber composite material. Background Art
[0002] With the explosive growth of the new energy vehicle industry, lightweighting has become a key demand in its development process. In line with this trend, the brake disc field has also embarked on a lightweight innovation journey, and the market demand for lightweight brake materials has risen. Among the many brake disc products, carbon ceramic brake discs, as a cutting-edge new generation product, have shown their advantages. On the one hand, it inherits the performance advantages of traditional high-quality brake discs in terms of high temperature resistance and wear resistance; on the other hand, its ultra-light weight characteristics are even more eye-catching, only one-third of the same size cast iron disc, and the lightweight requirements are easily met for it, which undoubtedly reduces the burden on the efficient operation of new energy vehicles.
[0003] In-depth exploration of the core structure of carbon ceramic brake discs shows that carbon fiber composite materials play a pivotal supporting role as a matrix, and the mainstream process for achieving its densification is chemical vapor deposition (CVI). Looking around the world, researchers have explored the potential of CVI technology and have successfully developed a variety of densification solutions to further optimize the performance of carbon ceramic brake discs.
[0004] At present, CVI densification mostly uses induction furnaces. Induction furnaces inevitably have uneven temperature field distribution. Especially when densifying large quantities and multiple columns, there will be obvious temperature differences between the top and bottom and inside and outside of the column. In addition, the temperature of the gas is low when it just enters the furnace, resulting in inconsistent CVI densification efficiency at each position, which in turn leads to uneven densification of a single plate and uneven densification at different positions of the column. People have tried other methods, mostly by changing the gas ratio and time. For example, a Chinese invention patent discloses a method for high-efficiency and low-cost CVI densification of carbon fiber preforms, which uses the addition of diluent gas, adjustment of the ratio of natural gas, propylene and nitrogen, and CVI time to complete a 150-hour deposition molding, and the final density reaches 1.30g / cm 3 . But it still can't solve this kind of problem very well. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the object of the present invention is to provide a method for rapid densification of carbon fiber composite materials.
[0006] The technical solution of the present invention is:
[0007] A method for rapidly densifying a carbon fiber composite material comprises the following preparation steps:
[0008] S1. Use resin spraying equipment to evenly spray the shaping agent on the surface of the carbon fiber preform, and perform low-temperature curing on the sprayed preform, with a curing temperature of 200-400°C and a curing time of 4-6h;
[0009] S2, arranging the carbon fiber preforms after low-temperature curing in step S1 into a column and placing them in a deposition furnace, introducing carbon source gas, and depositing them at 1010-1030° C. for 80-100 hours. When the deposition is completed and the preforms are taken out of the furnace, a line is marked on one side of the column, and the volume density is weighed;
[0010] S3. Load the furnace again, stack the carbon fiber preforms according to the density of medium, low and high, rotate them horizontally by 160-200° according to the marked positions, introduce the carbon source gas, and deposit them at 1020-1040°C for 120-150h.
[0011] Furthermore, the density of the carbon fiber preform in step S1 is 0.48-0.52 g / cm 3 .
[0012] Furthermore, the setting agent in step S1 includes the following components and their weight proportions:
[0013] 0-12 parts of epoxy resin, 0-14 parts of polyurethane resin, and 20-30 parts of vinyl resin.
[0014] Furthermore, the carbon fiber preforms are arranged into a material column, and its structure from bottom to top is: a supporting plate, a carbon fiber preform and a cover plate, wherein the supporting plate, the carbon fiber preforms, the preforms and the cover plate are separated by graphite gaskets.
[0015] Furthermore, in step S2, the carbon source gas is methane and propane, wherein the volume ratio of methane to propane is 4-6:1, and the deposition time is 85-95h.
[0016] Furthermore, during deposition in step S2, the pressure in the furnace is 3-5 kPa.
[0017] Furthermore, in step S3, the horizontal rotation is performed by 180°.
[0018] Furthermore, in step S3, the carbon source gas is methane and propane, wherein the volume ratio of methane to propane is 7:1, and the deposition time is 130-140 hours.
[0019] Furthermore, during deposition in step S2, the pressure in the furnace is 2-4 kPa.
[0020] The method of the present invention reduces the pre-deposition process and the possibility of deformation of the preform by hardening the preform before densification; the adjustment of the position and angle of the preform loaded twice can make the plate body densification more uniform, reduce the density difference of the whole furnace, make the density range more stable, and improve the consistency of the products of the whole furnace.
[0021] In the present invention, the first deposition stage is to make the density of the preform reach a fixed numerical range. In the second deposition stage, the deposition process is changed by adjusting the upper and lower positions and the horizontal positions of the carbon disk, which improves the uniformity of single-disk densification and reduces the density difference of the entire furnace disk.
[0022] The test shows that the method for rapid densification of carbon fiber composite materials of the present invention has a consistent densification range throughout the furnace, and the density difference of the whole furnace is ≤0.05g / cm 3 , the carbon disc has good densification uniformity, and the average dynamic balance of the carbon disc is ≤15g, which is significantly better than the products prepared by traditional processes. The densified carbon fiber preform can provide excellent mechanical performance guarantee for the carbon-ceramic brake disc. The tight fiber bonding of the densified carbon fiber preform gives the brake disc high strength and high stiffness, making it sufficient to cope with harsh braking conditions, effectively avoiding the brake disc from cracking and excessive wear under frequent braking, and greatly improving the reliability and durability of the brake disc. On the other hand, the good thermal conductivity characteristics of the densified carbon fiber preform can be fully utilized, and it can quickly conduct heat to ensure the timeliness and safety of vehicle braking.
[0023] Compared with the prior art, the method of the present invention has the following advantages:
[0024] The present invention innovatively proposes a rapid densification process for carbon fiber composite materials, which can significantly improve the uniformity of product density. Compared with traditional methods, it can effectively avoid the situation where the density difference of the whole furnace is too large and the density distribution of a single disk is uneven, effectively shorten the deposition time, and achieve uniform distribution of product density, thereby controlling the density difference of the whole furnace within a smaller range. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the structure of a single material column in Example 3 of the present invention;
[0026] Figure 2 A top view of a material column in a furnace plate in Example 3 of the present invention;
[0027] Figure 3 This is an electron microscope image of the thickness cross section of the preform after deposition in Example 3 of the present invention.
[0028] In the figure: 1. Support plate; 2. Carbon fiber preform; 3. Cover plate; 4. Graphite gasket; 5. Out-of-furnace mark position; 6. Furnace loading mark position. DETAILED DESCRIPTION
[0029] The present invention is further illustrated below through the description of specific implementation methods, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of the present invention, but as long as they do not deviate from the basic idea of the present invention, they are all within the protection scope of the present invention.
[0030] In the following examples and comparative examples, reagents not otherwise specified are conventional reagents and can be purchased from conventional reagent production and sales companies. The methods used are all prior art unless otherwise specified.
[0031] Embodiment 1 A method for rapidly densifying a carbon fiber composite material comprises the following preparation steps:
[0032] S1, select density of 0.48-0.52g / cm 3 A carbon fiber preform is prepared, and a setting agent is evenly sprayed on the surface of the carbon fiber preform by a resin spraying device, and the sprayed preform is low-temperature cured at a curing temperature of 200±20°C for 4 hours; wherein the setting agent (by weight) is 14 parts of polyurethane resin and 20 parts of ethylene resin;
[0033] S2, the carbon fiber preforms after low-temperature curing in step S1 are arranged into a column and placed in a deposition furnace, and methane and propane are introduced in a volume ratio of 4:1, and the deposition is carried out for 80 hours under a furnace pressure of 3.5 KPa and a temperature of 1010±5°C. When the deposition is completed and the preforms are taken out of the furnace, a line mark is made on one side of the column, and the volume density is weighed;
[0034] The material columns are placed at the four corners inside the furnace body, that is, in the form of four material columns; the structure of a single material column is, from bottom to top, a supporting plate 1, a carbon fiber preform 2 and a cover plate 3, wherein the supporting plate 1 and the carbon fiber preform 2, the carbon fiber preform 2 and the carbon fiber preform 2, and the carbon fiber preform 2 and the cover plate 3 are separated by graphite gaskets 4.
[0035] S3, re-loading the furnace, stacking the carbon fiber preforms 2 in the order of medium-low-high density, rotating them horizontally by 160° according to the marked positions, introducing methane and propane in a volume ratio of 6:1, depositing for 120 hours at a furnace pressure of 2.5 KPa and a temperature of 1020±5°C, and then taking them out of the furnace after the deposition is completed.
[0036] Example 2 A method for rapidly densifying a carbon fiber composite material comprises the following preparation steps:
[0037] S1, select density of 0.48-0.52g / cm 3 A carbon fiber preform is prepared, and a setting agent is evenly sprayed on the surface of the carbon fiber preform by a resin spraying device, and the sprayed preform is low-temperature cured at a curing temperature of 400±20°C for 6 hours; wherein the setting agent (by weight) is 12 parts of epoxy resin and 10 parts of polyurethane resin;
[0038] S2, the carbon fiber preforms after low-temperature curing in step S1 are arranged into a column and placed in a deposition furnace, and methane and propane are introduced in a volume ratio of 6:1, and the deposition is carried out for 100 hours under a furnace pressure of 3.5 KPa and a temperature of 1030±5°C. When the deposition is completed and the preforms are taken out of the furnace, a line mark is made on one side of the column, and the volume density is weighed;
[0039] The material columns are placed at the four corners inside the furnace body, that is, in the form of four material columns; the structure of a single material column is, from bottom to top, a supporting plate 1, a carbon fiber preform 2 and a cover plate 3, wherein the supporting plate 1 and the carbon fiber preform 2, the carbon fiber preform 2 and the carbon fiber preform 2, and the carbon fiber preform 2 and the cover plate 3 are separated by graphite gaskets 4.
[0040] S3, re-loading the furnace, stacking the carbon fiber preforms 2 in the order of medium-low-high density, rotating them horizontally by 200° according to the marked positions, introducing methane and propane in a volume ratio of 8:1, depositing for 150 hours at a furnace pressure of 2.5 KPa and a temperature of 1025±5°C, and then taking them out of the furnace after the deposition is completed.
[0041] Example 3 A method for rapidly densifying a carbon fiber composite material comprises the following preparation steps:
[0042] S1, select density of 0.48-0.52g / cm 3 A carbon fiber preform is prepared, and a setting agent is evenly sprayed on the surface of the carbon fiber preform by a resin spraying device, and the sprayed preform is low-temperature cured at a curing temperature of 300±20°C for 5 hours; wherein the setting agent (by weight) is 8 parts of epoxy resin and 26 parts of vinyl resin;
[0043] S2, the carbon fiber preforms cured at low temperature in step S1 are arranged into a column and placed in a deposition furnace, and methane and propane are introduced in a volume ratio of 5:1, and the deposition is carried out for 90 hours under a furnace pressure of 3.5 KPa and a temperature of 1020±5°C. When the deposition is completed and the preforms are taken out of the furnace, a line mark (e.g. Figure 2 The bulk density is measured at the middle exit mark position 5);
[0044] The material columns are placed at the four corners of the furnace body, that is, in the form of four material columns; the structure of a single material column is, from bottom to top, a support plate 1, a carbon fiber preform 2 and a cover plate 3, wherein the support plate 1 and the carbon fiber preform 2, the carbon fiber preform 2 and the carbon fiber preform 2, and the carbon fiber preform 2 and the cover plate 3 are separated by a graphite gasket 4, refer to Figure 1 shown.
[0045] S3, re-loading the furnace, stacking the carbon fiber preforms 2 in the order of medium-low-high density, and performing 180° horizontal rotation according to the marked positions (e.g. Figure 2At the mark position 6 in the middle loading furnace, methane and propane were introduced with a volume ratio of 7:1. The deposition was carried out for 135 hours under a furnace pressure of 2.5 KPa and a temperature of 1030±5°C. After the deposition was completed, the furnace was taken out of the furnace.
[0046] The thickness cross-section electron microscope image of the preform obtained in Example 3 after deposition is as follows: Figure 3 As shown, the black circle is long-fiber carbon fiber, and the white flake is deposited carbon. It can be seen from the figure that the carbon fiber is completely wrapped by the deposited carbon, and the carbon fibers are completely filled with the deposited carbon without pores, indicating that the densification uniformity is good and the density meets the standard.
[0047] Comparative Example 1 A method for rapidly densifying a carbon fiber composite material comprises the following preparation steps:
[0048] S1, select density of 0.48-0.52g / cm 3 The carbon fiber preform is sprayed evenly with a setting agent on the surface of the carbon fiber preform by a resin spraying device, and the sprayed preform is low-temperature cured at a curing temperature of 300±20°C for 5 hours; wherein the setting agent (by weight) is 6 parts of epoxy resin, 7 parts of polyurethane resin, and 30 parts of vinyl resin;
[0049] S2. Arrange the carbon fiber preforms after low-temperature curing in step S1 concentrically into material columns and place them in a deposition furnace, wherein the material columns are placed at the four corners inside the furnace body, i.e., in the form of four material columns; wherein the structure of a single material column is, from bottom to top, a support plate 1, a carbon fiber preform 2 and a cover plate 3, wherein the support plate 1 and the carbon fiber preform 2, the carbon fiber preform 2 and the carbon fiber preform 2, and the carbon fiber preform 2 and the cover plate 3 are separated by graphite gaskets 4; then, methane and propane are introduced in a volume ratio of 5:1, and the deposition is carried out for 230 hours under a furnace pressure of 3.5 KPa and a temperature of 1030±5°C, and the deposition is completed and the preform is cooled and taken out of the furnace.
[0050] Comparative Example 2
[0051] Compared with Example 3, the difference is that in step S3, the furnace is loaded again, and the material column is horizontally rotated 180° according to the marked position. Other components and preparation methods are the same as those in Example 3.
[0052] Comparative Example 3
[0053] Compared with Example 3, the difference is that, in step S3: the furnace is loaded again, the carbon fiber preforms 2 are stacked in the order of medium-low-high density, and are rotated horizontally by 180° according to the marked positions (refer to Figure 2 As shown in the figure, methane and propane are introduced in a volume ratio of 7:1, and the deposition is carried out for 135 hours under a furnace pressure of 3.5 KPa and a temperature of 1030±5°C. The other components and preparation method are the same as those in Example 3.
[0054] Comparative Example 4
[0055] Compared with Example 3, the difference is that, in step S3, methane and propane are introduced in a volume ratio of 7:1, and the deposition is carried out for 135 hours under a furnace pressure of 3.5 KPa and a temperature of 1030±5°C, and the deposition is completed and the furnace is taken out. The other components and preparation method are the same as those in Example 3.
[0056] Comparative Example 5 A method for rapidly densifying a carbon fiber composite material comprises the following preparation steps:
[0057] S1, select density of 0.48-0.52g / cm 3 The carbon fiber preforms are concentrically arranged into columns and placed in a deposition furnace. Methane and propane are introduced at a volume ratio of 5:1. The furnace is deposited for 60 hours at a furnace pressure of 3.5 KPa and a temperature of 1020±5°C, and then cooled.
[0058] The material columns are placed at the four corners of the furnace body, that is, in the form of four material columns; the structure of a single material column is, from bottom to top, a support plate 1, a carbon fiber preform 2 and a cover plate 3, wherein the support plate 1 and the carbon fiber preform 2, the carbon fiber preform 2 and the carbon fiber preform 2, and the carbon fiber preform 2 and the cover plate 3 are separated by a graphite gasket 4, refer to Figure 1 shown.
[0059] S3, introduce methane and propane with a volume ratio of 5:1, and deposit for 200 hours at a furnace pressure of 2.5 KPa and a temperature of 1030±5°C. After the deposition is completed, take the furnace out.
[0060] Comparative Example 6
[0061] Compared with Example 3, the difference is that step S1: selecting a density of 0.48-0.52 g / cm 3 A carbon fiber preform is prepared, and a shaping agent is evenly sprayed on the surface of the carbon fiber preform using a resin spraying device. The sprayed preform is low-temperature cured at a curing temperature of 500±20°C for 3 hours. The other components and preparation method are the same as those in Example 3.
[0062] Test Example 1: Performance test of carbon fiber preform prepared by the present invention
[0063] 1. Test object: carbon fiber preforms prepared in Examples 1 to 3 and Comparative Examples 1 to 6 of the present invention.
[0064] 2. Test objectives: To detect the average volume density of the carbon fiber preforms in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3, the densification difference of the whole furnace products, and the average dynamic balance of the carbon discs.
[0065] 3. Test method: The volume density is calculated by measuring the size of the carbon plate and weighing the weight of the carbon plate. The volume density is checked by the whole furnace. The density difference is the highest volume density minus the lowest volume density in the whole furnace. The dynamic balance value is measured by a dynamic balancing machine, and the whole furnace is checked, and then the dynamic balance average value is calculated. The results are shown in Table 1.
[0066] Table 1
[0067]
[0068] As shown in Table 1, the products obtained in Examples 1 to 3 of the present invention have more uniform densification, a smaller density difference throughout the furnace, a more stable density range, and improved consistency of the products throughout the furnace. The method for rapid densification of carbon fiber composite materials of the present invention has a consistent density increase throughout the furnace, and a density difference of ≤0.05 g / cm 3 , the carbon disc has good densification uniformity, and the average dynamic balance of the carbon disc is less than 15g, which is significantly better than the products prepared by the traditional process. The densified carbon fiber preform can provide excellent mechanical performance guarantee for the carbon-ceramic brake disc. The tight fiber bonding of the densified carbon fiber preform gives the brake disc high strength and high rigidity, which is sufficient to cope with harsh braking conditions, and effectively avoids the problems of cracking and excessive wear of the brake disc under frequent braking, greatly improving the reliability and durability of the brake disc. On the other hand, the good thermal conductivity characteristics of the densified carbon fiber preform are fully utilized, and it can quickly conduct heat to ensure the timeliness and safety of vehicle braking. In Comparative Examples 1 to 6, when the preparation process in the present invention was changed, the densification effect of the product decreased to varying degrees.
[0069] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for rapid densification of carbon fiber composite materials, characterized in that: The method comprises the following preparation steps: S1. Use resin spraying equipment to evenly spray the shaping agent on the surface of the carbon fiber preform, and perform low-temperature curing on the sprayed preform, with a curing temperature of 200-400°C and a curing time of 4-6h; S2, arranging the carbon fiber preforms after low-temperature curing in step S1 into a column and placing them in a deposition furnace, introducing carbon source gas, and depositing them at 1010-1030° C. for 80-100 hours. When the deposition is completed and the preforms are taken out of the furnace, a line is marked on one side of the column, and the volume density is weighed; S3, re-loading the furnace, stacking the carbon fiber preforms according to the density of medium-low-high, rotating them horizontally by 160-200° according to the marked positions, introducing carbon source gas, depositing them at 1020-1040°C for 120-150h, and cooling them out of the furnace.
2. The method for rapid densification of carbon fiber composite materials according to claim 1, characterized in that: The density of the carbon fiber preform in step S1 is 0.48-0.52 g / cm 3 .
3. The method for rapid densification of carbon fiber composite materials according to claim 1, characterized in that: The setting agent in step S1 includes the following components and their weight proportions: 0-12 parts of epoxy resin, 0-14 parts of polyurethane resin, and 20-30 parts of vinyl resin.
4. The method for rapid densification of carbon fiber composite materials according to claim 1, characterized in that: The carbon fiber preforms are arranged into a material column, and its structure from bottom to top is: a supporting plate, a carbon fiber preform and a cover plate, wherein the supporting plate, the carbon fiber preforms, the preforms and the cover plate are separated by graphite gaskets.
5. The method for rapid densification of carbon fiber composite materials according to claim 1, characterized in that: In step S2, the carbon source gases are methane and propane, wherein the volume ratio of methane to propane is 4-6:1, and the deposition time is 85-95 hours.
6. The method for rapid densification of carbon fiber composite materials according to claim 1, characterized in that: During deposition in step S2, the pressure in the furnace is 3-5 kPa.
7. The method for rapid densification of carbon fiber composite materials according to claim 1, characterized in that: In step S3, the image is rotated horizontally by 180°.
8. The method for rapid densification of carbon fiber composite materials according to claim 1, characterized in that: In step S3, the carbon source gases are methane and propane, wherein the volume ratio of methane to propane is 7:1, and the deposition time is 130-140 hours.
9. The method for rapid densification of carbon fiber composite materials according to claim 1, characterized in that: During deposition in step S2, the pressure in the furnace is 2-4 kPa.